INKLUSI KEUANGAN : DAMPAK LITERASI KEUANGAN, LITERASI KEUANGAN DIGITAL DAN FINANCIAL TECHNOLOGY PADA MAHASISWA: INKLUSI KEUANGAN : DAMPAK LITERASI KEUANGAN, LITERASI KEUANGAN DIGITAL DAN FINANCIAL TECHNOLOGY PADA MAHASISWA - Andriani, Sri (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2024)
Public access to financial institutions has decreased compared to the previous period. This decline indicates that society has not been able to use convenience, knowledge and effective supporting facilities to provide access to financial institutions. The aim of this research is to determine the impact of financial literacy, digital financial literacy and financial technology on student financial inclusion. The research method uses a purposive sampling method with data analysis using multiple linear regression. The research results show that financial literacy does not have a significant effect on financial inclusion. Meanwhile, digital financial literacy and dan financial technology have a significant influence on changes in financial inclusion for students.